Critical Clinical forms of influenza AH1N1: What we have learned from assisting the ill in Cienfuegos. - Grupo Operativo Provincial de Atención Médica a los enfermos adultos hospitalizados (Medisur)
We currently possess a growing information level on the effects of the influenza AH1N1epidemics in a range of countries in the world. Much of that information refers to statistical data and recommendations for dealing with it. Concerning the clinics of the infected, the existence of groups presenting risks of complications has been repeatedly noted in the international literature, as well as critical clinical findings, with unusual manifestations in other epidemics caused by influenza viruses. To that effect, an approach to characterize various clinical-radiological forms of that entity, as well as serious complication risk groups, may help in the early diagnose and appropriate treatment, which, undoubtedly, along with keeping preventive measures, constitute the best form of assisting the ill in the epidemic phase.